Insect evolution in an amberiferous and stone alphabet : proceedings of the 6th International Congress on Fossil Insects, Arthropods and Amber - Azar, Dany, 1973- (Brill, 2013)
Insects are the most diverse group of life on Earth and their history extends well into the Paleozoic, making them among the oldest of terrestrial animal lineages. They are critical to the well being of ecosystems from the equator to the poles, and are inexorably tied to the well being of our world. Whether beneficial or malignant, insects wield an overwhelming influence on our health, economy, and security. It is little wonder that insects so consistently appear in our cultures, religions, and mythologies. Given such realities, it is vital that we gain a better understanding and appreciation of Nature's 'inordinate fondness'. Indeed, there is considerable wisdom to be found in the study of these marvels of evolution, and what better way to understand their present and future than to peer back into their distant past. Here presented are some of the results of the 6th International Congress on Fossil Insects, Arthropods and Amber (FossilX3) held in Byblos, Lebanon in April, 2013. In the tradition of previous congresses, researchers from around the world gathered to discuss the latest developments and to build new co-operative endeavours. Recognizing that the future of our science is one of interdisciplinary collaboration, these meetings steadily grow in importance, and proceedings such as this reveal the latest hypotheses and conclusions, while inspiring others toward newer and greater goals.